2017
DOI: 10.1186/s13037-017-0133-1
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing factors for recurrence of chronic posttraumatic osteomyelitis: a retrospective observational cohort study from a tertiary referral center in Brazil

Abstract: BackgroundThe incidence of posttraumatic osteomyelitis (PTO) is increasing despite new treatment strategies. Assessment of patients’ outcomes following PTO is challenging due to multiple variables. The study goals are to determine the frequency of recurrence following PTO treatment and identify factors predisposing patients to treatment failure.MethodsBetween August 01, 2007 to August 30, 2012, a single-center retrospective cohort study was performed among 193 patients diagnosed with PTO following orthopedic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 36 publications
3
13
1
Order By: Relevance
“…In our study, 60.5% of S. aureus isolated were resistant to oxacillin. Although we observed a slight decline over the study period, this proportion is higher than that reported in recent series of PTO in Brazil (35.5%) and in China (35.9%) [3, 4]. Resistance to other drugs of interest frequently used for osteomyelitis was also common in our patients.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…In our study, 60.5% of S. aureus isolated were resistant to oxacillin. Although we observed a slight decline over the study period, this proportion is higher than that reported in recent series of PTO in Brazil (35.5%) and in China (35.9%) [3, 4]. Resistance to other drugs of interest frequently used for osteomyelitis was also common in our patients.…”
Section: Discussioncontrasting
confidence: 76%
“…This group of bacteria was involved in 2.8% of 142 PTO in one American trauma center [6], but in 35.5% of cases in another recent study in China where patients, like those in the Amman MSF program, were frequently suffering from open fracture and/or soft tissue damage following direct trauma [4]. P. aeruginosa was frequent in our study (13.5% of isolates); this is worrisome for PTO patients in Amman given the fact that infections with P. aeruginosa have been found to be associated with increased risk of recurrence of osteomyelitis [3, 6].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In this study, 52.94% (9/17) of patients with recurrence of infections received intraoperative blood transfusion, which was much higher than 22.73% (30/132) of the non-infection recurrence group. In an analysis of 192 patients with post-traumatic osteomyelitis, risk factors for recurrence of infection were analyzed which showed that the risk of infection recurrence in patients receiving blood transfusion was 2 times higher [26] , which is similar to our study. Another study proposed that the risk of multi-microbial infection in patients undergoing blood transfusion during orthopedic surgery is 2.15 times higher than that of patients without blood transfusion [29] .…”
Section: Discussionsupporting
confidence: 87%
“…Recent studies have suggested that Pseudomonas aeruginosa is directly related to the recurrence of posttraumatic osteomyelitis infection [26] . In summary, in charge surgeon need to be alerted to patients with posttraumatic tibial osteomyelitis caused by Pseudomonas aeruginosa infection…”
Section: Discussionmentioning
confidence: 99%